Organic Fertilizer Based on Rhizophagus intraradices: Valorization in a Farming Environment for Maize in the South, Center and North of Benin - Aguégué, Ricardos M.; Assogba, Sylvestre A.; Salami, Hafiz A. A.; Koda, Abdel D.; Agbodjato, Nadège A.; Amogou, Olaréwadjou; Sina, Haziz; Salako, K. Valère; Ahoyo Adjovi, Nestor R.; Dagbénonbakin, Gustave; Kakai, Romain Glélé; Adjanohoun, Adolphe; et al. (Frontiers in Sustainable Food Systems, 2021)
Maize plays an important role in agricultural production systems in all agro-ecological zones of Benin. Despite its importance, its production faces many constraints including soil fertility. One of the ecological technologies aimed at improving agricultural production is the use of soil microorganisms including arbuscular mycorrhizal fungi (AMF). This study aims to evaluate the effectiveness of Rhizophagus intraradices, an indigenous strain, on maize productivity in farmers' areas in the Research and Development (RD) sites of the North (Ouénou), Center (Miniffi), and South (Zouzouvou). Three maize producers were selected at each RD site, for nine maize producers. The experimental design was a randomized complete block of three treatments with three replications. The different treatments were (i) Control–farmer's practice, (ii) R. intraradices + 50% of the recommended dose of NPK and urea, and (iii) 100% of the recommended dose of NPK and urea. Soil samples from the different RD sites were taken at a depth of 0–20 cm before sowing for chemical analysis. The different growth parameters (height, crown diameter, and leaf area), grain yield, and endomycorrhizal infection of maize plants were evaluated. The results showed that the soils were moderately acidic (5.5 ≤ pH waters ≤ 6.8) and low in organic matter (0.95 ≤ 33 OM ≤ 1.17) regardless of the study area. The greater maize grain yield was recorded with application of 100% of the recommended dose of NPK and urea, and R. intraradices + 50% of the recommended dose of NPK and urea. In the RD sites at the South, Center, and North recorded with R. intraradices + 50% of recommended dose of NPK and urea, the grain yields of 1.9, 3.4, and 1.74 t/ha with an increase of 28, 38.21, and 13.21%, respectively, compared with farmer's practice. Mycorrhization frequencies in plants treated with Ri¹ N15P15K15 vary between 37.44 and 51.67% in the three zones. The results of the current study have proven the potential use of R. intraradices in sustainable intensification of maize production in Benin.